STUDENTS PERCEPTION OF SCIENTIFIC WRITING CLASS ON THEIR LEARNING GAINS - Siti Masniah; M. Zaini Miftah; Aris Sugianto (PROJECT (Professional Journal of English Education), 2021)
The research was carried out in order to know the students perception of scientific writing class on their learning gains. The sample were taken based on random technique. This research used quantitative approach. The research design of this study was survey research. These reserach subjects were 105 participants in semester 6th and 8th students English Education study program. The data were analyzed using Ms. Excel and SPSS 24 Program. The data in this research collected by using questionnaire as main instrument. The result of the study got  90%  integrate sources, 89% research 86% structure, 91%  feedback, 85% technique, 87% review, 81% research plan. This research showed that students gave positive responses with very good category of the scientific writing course on their learning gains to improve students writing skills. Most of the students in the scientific writing class have studied all the materials, strategies, and students are able to understand the writing tasks that have been given by the lecturer in improving scientific writing skills such as writing essays, abstracts, and thesis proposals. The respondents agree that the scientific writing is a learning material that affects the progress student of learning gains in writing scientific papers. Keywords:  Students Perception, Scientific Writing, Learning Gains